Isolation, identification and molecular characterization of Mycoplasma bovis in mastitic dairy cattle by PCR and culture methods - IMANDAR, M.; POURBAKHSH, S. A.; JAMSHIDIAN, M.; ZAHRAEI SALEHI, T. (Journal of the Hellenic Veterinary Medical Society, 2018)
Mycoplasma bovis is well known as one of the major causative agents of mastitis in dairy cattle herds. The aim of this study was the identification of Mycoplasma bovis strains by PCR and traditional culture methods from a total number of 328 milk samples collected from cows with clinical mastitis symptoms from all over Iran. First step cultures in PPLO broth and agar showed 58 samples (17.69%) as positive. Out of 328 samples, 97 samples (29.57%) were positive for Mycoplasma genus according to the amplification of the 16SrRNA gene performed by PCR and from them, 31 (31.97%) samples were positive by PCR on the P48 gene. The purified P48 positive PCR products were sequenced and results were compared to M. bovis reference strain PG45 (CP002188). A phylogenic tree was created using Neighbor-joining method in MEGA6 software. The studied strain IB220 showed 100% identity with the reference strain of M. bovis and followed the same phylogenetic roots while studied strain IB216 showed 99.7% homology with the reference strain. Twelve selected geographical isolated strains were subjected to Gene Bank under accession numbers of KX772789 to KX772800. This is the first study of the molecular characterization of Mycoplasma bovis in dairy cattle with clinical mastitis from Iran.